Quality Improvement Planning Based on School Development Plan at MTs Ihyaul Ulum Gresik - Dewanti, Almira Annora; Handayaningrum, Warih; Roesminingsih, MV (Science Education and Application Journal, 2022)
At MTs Ihyaul Ulum Gresik, quality improvement planning is based on the school development plan. This study is being conducted at MTs Ihyaul Ulum Gresik. The emphasis of this research is on planning for increasing educational quality based on work programs included in MTs Ihyaul Ulum Gresik's school development plan for 2020/2021 and their relationship to eight national education standards. A document study was employed to obtain data for this investigation. MTs Ihyaul Ulum Gresik's school development plan for 2020/2021 is being examined. This study's data were reported utilizing a qualitative descriptive technique. The findings of this study include the quality improvement plans identified in the work program of MTs Ihyaul Ulum Gresik, which are divided into three time periods: short (annual), medium (four years), and long (eight years). Because such work programs were related to eight national education standards, not all national education standards were found in MTs Ihyaul Ulum Gresik's work program. Some national education criteria are not present in the MTs Ihyaul Ulum Gresik job program.